Functional brain organization of working memory in adolescents varies in relation to family income and academic achievement. Issue 5 (19th July 2016) - Finn, Amy S.; Minas, Jennifer E.; Leonard, Julia A.; Mackey, Allyson P.; Salvatore, John; Goetz, Calvin; West, Martin R.; Gabrieli, Christopher F.O.; Gabrieli, John D.E.
Abstract: Working memory (WM) capacity reflects executive functions associated with performance on a wide range of cognitive tasks and education outcomes, including mathematics achievement, and is associated with dorsolateral prefrontal and parietal cortices. Here we asked if family income is associated with variation in the functional brain organization of WM capacity among adolescents, and whether that variation is associated with performance on a statewide test of academic achievement in mathematics. Participants were classified into higher‐income and lower‐income groups based on family income, and performed a WM task with a parametric manipulation of WM load (N‐back task) during functional magnetic resonance imaging (fMRI). Behaviorally, the higher‐income group had greater WM capacity and higher mathematics achievement scores. Neurally, the higher‐income group showed greater activation as a function of WM load in bilateral prefrontal, parietal, and other regions, although the lower‐income group exhibited greater activation at the lowest load. Both groups exhibited positive correlations between parietal activations and mathematics achievement scores, but only the higher‐income group exhibited a positive correlation between prefrontal activations and mathematics scores. Most of these findings were maintained when higher‐ and lower‐income groups were matched on WM task performance or nonverbal IQ. Findings indicate that the functional neural architecture of WM varies with family income and is associated with education measures of mathematics achievement. Abstract : Higher versus lower family income in adolescents was associated with higher scores on a statewide mathematics achievement test, greater working memory capacity, greater functional brain responses to increasing memory demands, and differential brain correlations with achievement. Findings indicate that the functional neural architecture of working memory varies with family income and is associated with achievement.